Islam and international relations fractured worlds - Pasha, Mustapha Kamal (Oxon Routledge, 2017)
"Islam and International Relations: Fractured Worlds reframes and radically disrupts perceived understanding of the nature and location of Islamic impulses in international relations. This collection of innovative essays written by Mustapha Kamal Pasha presents an alternative reading of contestation and entanglement between Islam and modernity."--Provided by publisher.
Includes bibliographical references (pages 154-172) and index.
Keywords: Islam and international relations; Islamic countries -- Foreign relations -- Western countries; Western countries -- Foreign relations -- Islamic countries